Baobab bark (Adansonia digitata) - Romero, C.; Grundy, I.; Campbell, Bruce M.; Cunningham, A.B. (Routledge, 2002)
This chapter provides short description of the plant, its variety of products from its bark, the wood and seed. Further it provides a brief information on the ecology and the impact of bark harvesing by the local people and other stresses. One of the studies reported that harvesting was more prevalent during the dry season when people had available time due to reduced agricultural activites. Despite traditional rules governing over baobab harvesting the practice of overharvesting has been widespread in the study area.Problems with managing baobab bark are currently being exacerbated by weak institutions and poverty. This chapter concludes that under present conditions, the potential for certification of baobab bark is low.